Multiple cavernous hemangiomas of the orbit: Separate occurrence within a 24-year period - Nagulić Mirjana; Nikolić Igor; Manojlović-Gačić Emilija; Skender-Gazibara Milica (Vojnosanitetski Pregled)
Background. Cavernous hemangioma is a frequent and the most common, primary, benign tumor of the orbit in adults. It is typically single and unilateral, considered not to recur after having been completely excised. Multiple orbital cavernous hemangiomas without signs of hemangiomatosis are rare. Multiple cavernous hemangiomas may recur after a complete excision and may exist with concurrent systemic tumors. Tumor recurrence is supposed to develop from vasculature that is present already in response to a proliferate stimulus. Case report. A 39-year old female with painless proptosis of the right orbit was found to have four orbital tumors. The first orbitotomy was performed in 1984 by excising four cavernous hemangiomas. Six years later, another, the fifth one cavernous hemangioma was totally excised from the same orbit. Nine years after the first operation, reorbitotomy was performed because of positive radiological and clinical signs of de novo tumor in the orbit. The operation did not confirm the tumorous tissue. The fourth orbitotomy was performed 24 years after the first operation and two cavernous hemangiomas were totally excised. Conclusion. This case show the possibility of cavernous hemangioma recurrence after a previously totally excised tumor, separated more than two decades. A very long follow-up of the patients operated for these benign tumor lesions is recommended.